Motivation and determinants of research careers among physicians: Exploring pros and cons of the Dutch MD-PhD model - Margot M. Weggemans; Frank J. Wolters; Rinze Benedictus; Berent Prakken; Olle ten Cate; Helena J.M. Pennings (PLoS ONE, 2026)
Introduction Training pathways, such as MD-PhD-programs, have been established to increase the physician-scientist workforce. Still, MD-PhDs represent only a small fraction of the physician workforce worldwide. This is different in the Netherlands, where half of specialist physicians hold a PhD, but little is known about their careers. We aimed to explore the motivations of Dutch physicians to pursue a PhD, and investigate the proportion of MD-PhDs entering physician-scientist careers. Methods In 2022, we conducted a survey study among all MD-PhDs in the Netherlands who obtained a PhD degree in the year 2008. Drawing on self-determination theory, we used the Motivation for PhD Studies Scale to assess respondents’ motivations for pursuing a PhD. We defined a physician-scientist career as spending at least 20% of working hours on both research and clinical work. Results Of all 479 MD-PhDs, 240 completed the survey (response rate 56.6%). Motivation for a physician-scientist career appeared to be predominantly driven by autonomous motivation (including intrinsic and internalized forms of extrinsic motivation), rather than controlled motivation (reflecting external and internal pressures). Of all respondents, 67.5% reported a combination of clinical and research activities. One quarter (25.2%) met our criteria for a physician-scientist career, similar between men and women. Higher scores for autonomous motivation were associated with continued research activity, including a physician-scientist career and tenured appointment. The motivation to pursue research and having a scientific network or research collaborations were mentioned as supportive factors for continuing research after the PhD. The lack of dedicated time for research and a desire to spend more time with one’s partner or family were the most important barriers against continued research activities. Conclusions Autonomous motivation is more important than controlled motivation for Dutch physicians in pursuit of a PhD, and is associated with an increased likelihood of a subsequent physician-scientist career. Of the large proportion of MD-PhDs in the Dutch physician workforce, one fourth continues as physician-scientist.